2017
DOI: 10.4000/sociologico.1829
|View full text |Cite
|
Sign up to set email alerts
|

Employability of higher education graduates in Spain: crisis and new challenges

Abstract: This article analyses the employability of university graduates in Spain, in terms of both the quantity and quality of employment. Regarding quantity, graduate employment rates are higher than those for people with other education levels. Furthermore, both in times of crisis and of bonanza, graduates are more protected against unemployment. This is fundamentally due to the fact that they work in sectors and occupations that are less exposed to cycles. Regarding the quality of their jobs, graduates are less lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…I focus on this group of educationally advantaged young people as an extreme case; Spain is one of the developed countries with the most pervasive unemployment and employment precarity among highly educated young adults (Emmenegger et al, 2012;Mart ınez-Pastor, 2017). Nonetheless, this case highlights an increasingly pressing issue worldwide.…”
mentioning
confidence: 99%
“…I focus on this group of educationally advantaged young people as an extreme case; Spain is one of the developed countries with the most pervasive unemployment and employment precarity among highly educated young adults (Emmenegger et al, 2012;Mart ınez-Pastor, 2017). Nonetheless, this case highlights an increasingly pressing issue worldwide.…”
mentioning
confidence: 99%
“…hen examining the situation of women in the context of transition studies, and in particular the move from training to the labour market, it can be observed that the way is paved with inequalities and instability from the very start of contact with the world of work. In Spain, these work-related issues become yet more serious when we compare women with their male counterparts, particularly if we take into account that women are educated to a higher level, are in the majority at nearly all levels of the education system and obtain better academic results (Gutiérrez-Esteban & Luengo-González, 2011;Martínez-Pastor, 2017).Thus, concerning the developed world, we can refer to the paradox between the academic level reached by women and the roles that they occupy in society, while we can also see that, both nationally and internationally, horizontal and vertical segregation remains unchanged throughout the majority of highereducation systems (Charles & Bradley, 2009;Tellhed, Backstrom, & Bjorklund, 2017). This phenomenon is reflected in the job market: women's entry into the working world has been a trend over the last few decades, not only due to the structure of the economy itself but also as a result of the attitudes and behaviour of social and economic agents, which are reproduced in the organisation of society and family life.…”
Section: Hernández-rincón -Digital Inclusionmentioning
confidence: 99%